REAKTUALISASI NILAI PENDIDIKAN BERBASIS STEAM SEBAGAI UPAYA MENYONGSONG INDONESIA EMAS 2045: Pengabdian Masyarakat - Resmi; Asriadi; A. Dwi Putri Astrifa Sufina Ahmad; 4Husnul Fadhilah Ham; Jumriana; Nur Ainun; Nurkhaerah; Reski Amalia; Abdul Gaffar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Education is a cornerstone of national development and a fundamental right guaranteed by the Indonesian Constitution. However, challenges such as limited access, low economic conditions, and inadequate educational facilities remain significant barriers, particularly in marginalized areas like Kampung Savana, Makassar. This study aims to implement a STEAM-based education approach (Science, Technology, Engineering, Arts, Mathematics) to enhance the academic and social skills of children in this community. Using a descriptive qualitative method and participatory action research, the study involved 28 children aged 7–14 years, along with parents, educators, and facilitators. The results revealed that approaches through Creative Corner, Cultural Corner, and Play Corner successfully increased learning motivation, basic skills, creativity, and understanding of local cultural values. Despite limitations in resources, the STEAM-based education approach proved effective in creating an inclusive and relevant learning environment, supporting the vision of Indonesia Emas 2045